Geographical Indication (GI) in Sri Lanka: A scientometric study of scholarly output - Rajkumar, N.; Suresh, N.; Sankar, M. (University of Jaffna, 2022)
The study examines Sri Lanka’s research on Geographical Indication (GI) by an alyzing the research articles indexed on the Web of Science (WoS) between 1989 and 2021. During this time, the researchers produced a total of 100 articles in the field of geographic indication. Each year, an average of 4.3 publications were published. The most articles were published in 2021, with 16 publications and 18 citations, and the most citations were received in 2006, with 326 citations. There were only six articles with 225 citations in 2016. With 12 papers and 210 citations, Germany came out on top in the collaborative, followed by Italy (08 articles and 208 citations), which was the most collaborative country according to citations. The USA contributed seven articles and received 467 citations. India and Sri Lanka collaborated on two articles. Bandaranayake PCG, Favaro-Trindade CS, Katulanda P, and Ranasinghe P are the most prolific authors, with four articles each, but these two authors, Katulanda, P and Ranasinghe, P received 183 citations. The article that received the highest citations is “The cupric ion reducing antioxidant capacity and polyphenolic content of some herbal teas”, and it received 294 citations.
Keywords: Intellectual property rights; Bibliometrics; Citation analysis; Scientometrics